Observed automobile drivers' mobile phone use rates in Ibadan metropolis, Nigeria (2015)
The use of mobile phone while driving is a growing problem in both developed and developing countries. This problem was investigated among automobile drivers through fixed location observational survey in three residential densities in Ibadan Metropolis. The survey was undertaken for seven days between 7.00am and 7.00pm everyday. Both descriptive and inferential statistics were used for data analysis. The average phone use rates in low, medium and high densities were 4.3%, 4.2% and 4.2% respectively. Daily pattern showed two peak periods coinciding with the conventional traffic volume peaks in all the zones. Also, drivers were more likely to use mobile phones 2 times during. weekdays compared to weekends. Males were five times more likely to use cell phone than females. One-way ANOVA showed significant difference (p> 0.05) in the use of mobile phones among automobile drivers across the week. The paper advocates increased enlightenment on the dangers of phone use behind the wheels, improved surveillance, proper enforcement of existing legislation banning phone use while driving as well as tougher penalties.